Estimation of gingival crevicular fluid aspartate aminotransferase levels in periodontal health and disease - Priti B Patil; Basgauda Patil (Wolters Kluwer Medknow Publications, 2011)
Background: Various enzymes have been assessed as biochemical markers and aspartate aminotransferase (AST) is one such marker that has received considerable attention recently. Analysis of gingival crevicular fluid (GCF) has been pursued as a means of identifying the sites undergoing active disease. A problem central to periodontology today is the inability to detect actively deteriorating sites and highly susceptible patients other than by longitudinal observations of attachment. Hence, AST levels from samples of GCF can be taken as an indication for active periodontal tissue destruction. Aim: To estimate the levels of AST in the GCF in periodontal health and disease. Materials and Methods: This study was an in vivo, case control, and clinico-biochemical assay. Eighty samples were selected which were divided into four groups of 20 patients each based on Russell's Periodontal Index. Statistical analysis: The values obtained for AST level in the different groups were subjected to Student's " t" test. Results: The mean of AST level showed an increase from Group I to Group IV. These values ran parallel with the values of clinical index, i.e. more severe the inflammation, higher the index score and higher was the AST level. Conclusions: It was concluded that as the severity of inflammation increases, there is a significant increase in the AST levels suggesting that there is a direct relationship between the AST levels in the GCF and periodontal destruction.